EFFECT OF BORON ON SOME INDUSTRIAL CROPS: A REVIEW - Waleed Al-Juheishy (Mesopotamia Journal of Agriculture)
Boron is considered one of the necessary elements for the growth of plants, it participates in the process of pollination, fertilization and plant fruit setting. It enhances the formation of adenosine triphosphate (ATP) and serves as a compound that accelerates the movement of sugars into the active areas during growth throughout the reproduction stages of the plant. Shortage in boron causes slowness in plant growth, decrease in production and degradation of crops quality. It is found that adding boron to some industrial crops such as (sesame, sunflower, safflower, rapeseed, soybean, cotton, flax, and sugar beet) leads to stimulating plants, accelerating the growth, and increasing the production of these crops, through its influence on many physiological functions that determine the growth and development of crop yield. It was noted that boron facilitates and speeds the transfer of sugars to the plants, as it interacts with sugars, forming a sugar complex with boron, this works on the movement of boron through cell membranes with ease compared to the movement of sugar molecules alone, and this may be due to the formation of regions or points of reception of sugar in modern growth or because boron may be considered one of the components of plant membranes, It also works to regulate enzymatic activity.